Virtù e valori etici della Diatriba. Un tributo a Bernardino Ramazzini in occasione del trecentesimo anniversario della morte (1714) / Ethical values and virtues of the Diatriba. A tribute to Bernardino Ramazzini on the tercentenary of his death (1714) - Franco, Giuliano (La Medicina del Lavoro, 2014)
Summary «Ethical values and virtues of the Diatriba. A tribute to Bernardino Ramazzini on the tercentenary of his death (1714)». Based on Hyppocratic values ​​of ancient medicine, Ramazzini’s way of thinking prefigures the social medicine that was to be an achievement of the Enlightenment. This contribution aims at analyzing the ethical aspects of the Diatriba. The preface already contains elements that constitute the ethical manifesto of Ramazzini. He shows compassion (”…we must admit that the workers in certain arts and crafts sometimes derive from them grave injuries”), expresses gratitude (”we owe this to the wretched condition of the workers from whose manual toil…so many benefits accrue”), demonstrates a sense of justice (“ …in our own time also laws have been passed in well-ordered cities to secure good conditions for the workers; so it is only right that the art of medicine should contribute its portion for the benefit and relief of those for whom the law has shown such foresight”) and demonstrates his willingness to be helpful to workers (“…I have tried to unearth in the shops of craftsmen…to suggest medical precautions for the prevention and treatment of such diseases as usually affect the workers”). The ethical contribution of Ramazzini, however, goes far beyond these noble and heartfelt words, demonstrating his intellectual and moral depth. In fact, alongside comments and suggestions, quotations and proposals, information and warnings, the Magister offers a framework for his beliefs on the attitude that the physician should adopt. Prudence and moderation inspire his recommendations when he speaks directly and indirectly to workers; irony and sarcasm pervade his thoughts when he talks to his colleagues, fairness and integrity inspire his remarks to authorities. Although current practice is based on ethical rules dating back to more recent times, the ethical vision of the Magister, that is admirable for its honesty, originality and depth, is in some respects still relevant today. Riassunto Fondato sui valori ippocratici della medicina antica, il pensiero ramazziniano prefigura la medicina sociale che sarà una conquista del secolo dei lumi. Il contributo si prefigge di analizzarne gli aspetti etici alla luce dei canoni moderni. Già nella prefazione la Diatriba contiene gli elementi che costituiscono il manifesto etico di Ramazzini che dimostra compassione ed esprime gratitudine, testimoniando senso di giustizia e rivelando la volontà di essere utile ai lavoratori. Il contributo etico tuttavia va ben oltre le nobili e accorate parole contenute nella prefazione; in tutto il testo il Magister, accanto a osservazioni e suggerimenti, a citazioni e proposte, a indicazioni e ammonimenti offre un affresco delle proprie convinzioni sul comportamento che ogni medico deve tenere. Prudenza e moderazione ispirano le indicazioni che Ramazzini rivolge direttamente e indirettamente ai lavoratori; ironia e sarcasmo pervadono i moti d’animo che spesso rivolge ai colleghi; equità e integrità ispirano i richiami ai sovrani. Anche se i principi etici e le regole su cui è basata oggi la pratica professionale risalgono a tempi più recenti, la visione etica del Magister, ammirevole per onestà, originalità e profondità, è per alcuni aspetti ancora attuale.